2020
DOI: 10.1108/jbs-04-2020-0078
|View full text |Cite
|
Sign up to set email alerts
|

The succession dilemma in family firms: case study of a French company

Abstract: Purpose The purpose of this paper is to highlight the major difficulties and challenges encountered during the crucial process of family succession. In this study, the authors list and analyze issues encountered by managers or by the CEO of a family business. Design/methodology/approach Using a single longitudinal real-time case study conducted over a period of 10 years in a French family business, this study identifies the challenges encountered during family succession. The authors were allowed to follow, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…According to Bose and Pal (2020), a caring and compassionate family structure plays a major role in helping employees improve their resilience. Meier and Thelisson (2021), to be a strong predictor of work-to-family enrichment, highlighting its signi􀅫icance for the harmonious coexistence of work and family life, have found family support. Furthermore, having the impression that one's family is there to assist one helps one deal with obstacles at work.…”
Section: Mediating Role Of Perceived Family Supportmentioning
confidence: 97%
See 1 more Smart Citation
“…According to Bose and Pal (2020), a caring and compassionate family structure plays a major role in helping employees improve their resilience. Meier and Thelisson (2021), to be a strong predictor of work-to-family enrichment, highlighting its signi􀅫icance for the harmonious coexistence of work and family life, have found family support. Furthermore, having the impression that one's family is there to assist one helps one deal with obstacles at work.…”
Section: Mediating Role Of Perceived Family Supportmentioning
confidence: 97%
“…According to Meier and Thelisson (2021), "innovations that give advantages would have a more widespread and quick pace of diffusion." These advantages include perceived compatibility with existing practices and beliefs, minimal complexity, potential liability, and observability.…”
Section: Underpinning Theorymentioning
confidence: 99%
“…In depth studies have demonstrated that government support, strategy and management, technology usage, succession issues, female role in family business, societal issues, leadership capability, distinctiveness, and so on are the most vulnerable research areas needed to be thoroughly drilled in Ratten et al (2017a, b), Ramadani et al (2017). So, the present study has taken a holistic attempt to analyse how government support and technology usage by the family business enterprises could influence the intention of the family business entrepreneurship irrespective of the gender of the family entrepreneurs (Meier and Thelisson, 2021). Also, attempt has been taken to investigate how the impacts of government support and technology usage can influence the entrepreneurial intention under the moderating effects of genderism since gender-oriented studies are perceived to have strengthened family business studies.…”
Section: Introductionmentioning
confidence: 98%
“…(2017). So, the present study has taken a holistic attempt to analyse how government support and technology usage by the family business enterprises could influence the intention of the family business entrepreneurship irrespective of the gender of the family entrepreneurs (Meier and Thelisson, 2021). Also, attempt has been taken to investigate how the impacts of government support and technology usage can influence the entrepreneurial intention under the moderating effects of genderism since gender-oriented studies are perceived to have strengthened family business studies.…”
Section: Introductionmentioning
confidence: 99%